Valsartan/2-Aminopyridine Co-Amorphous System: Preparation, Characterization, and Supramolecular Structure Simulation by Density Functional Theory Calculation - Linjie Wang; Chunan Du; Yang Yang; Pengtu Zhang; Shiling Yuan (Molecules)
The objective of this work was to improve the solubility and discover a stable co-amorphous form of valsartan (VAL), a BCS class-II drug, by utilizing small molecule 2-Aminopyridine (2-AP) in varying molar ratios (2:1, 1:1, and 1:2), employing a solvent evaporation technique. Additionally, by way of a density functional theory (DFT)-based computational method with commercially available software, a new approach for determining the intermolecular connectivity of multi-molecular hydrogen bonding systems was proposed. The binary systems’ features were characterized by PXRD, DSC, FTIR, and Raman spectroscopy, while the equilibrium solubility and dissolution was determined in 0.1 N HCL and water conditions to investigate the dissolution advantage of the prepared co-amorphous systems. The results demonstrated that the co-amorphous system was successfully prepared in VAL/2-AP with a 1:2 molar ratio following solvent evaporation, whereby the hydrogen bonding sites of VAL were fully occupied. Physical stability studies were carried out under dry conditions at room temperature for 6 months. Furthermore, four possible ternary systems were constructed, and their vibrational modes were simulated by DFT calculations. The calculated infrared spectra of the four configurations varied widely, with trimer 1 showing the most resemblance to the experimental spectrum of the co-amorphous 1:2 system. Additionally, co-amorphous VAL/2-AP displayed significant improvement in the solubility and dissolution study. Notably, in the 1:2 ratio, there was almost a 4.5-fold and 15.6-fold increase in VAL’s solubility in 0.1 N HCL and water environments, respectively. In conclusion, our findings highlight the potential of co-amorphous systems as a feasible approach to improving the properties and bioavailabilities of insoluble drugs. The proposed simulation method provides valuable insights into determining the supramolecular structure of multi-molecular hydrogen bonding systems, offering a novel perspective for investigating such systems.